The influence of price, promotion, and product quality on purchase decisions at PT Karsa Primapermata Nusa - Lisa Sien Tiani; Angelique Albertina Laurence; Nicky Irawan; Vincent Darma Saputra; Januardin Januardin (Privietlab, 2023)
This research aims to test and analyze the influence of price, promotion, product quality, and purchase decisions. Decreased purchasing decisions have occurred in the company due to a decrease in company income. In the pricing phenomenon, special prices are offered only to loyal customers who have been purchasing products for a minimum of 2 years. New customers, on the other hand, do not receive any price discounts. In terms of promotional activities, the company's efforts have been inadequate, primarily relying on personal selling by salesmen every month who offer products to customers. Product returns are still frequent, and customers often complain about the product's durability, which tends to be short. This research employs a quantitative approach with a sample of 100 customers. Multiple linear regression is used for data analysis. Simple random sampling is used as the sampling method. The conclusion of this research is that price has a positive and significant influence on purchase decisions, promotion has a positive and significant influence on purchase decisions, and product quality has a positive and significant influence on purchase decisions. In the case of price, promotion, and product quality variables, they all have a positive and significant impact on purchase decisions with a coefficient of determination of 35%.